A NARRATIVE REVIEW ON FORENSIC PHARMACOKINETICS AND ITS SCOPE (The Research of Medical Science Review, 2025)
Background: Forensic pharmacokinetics refers to the study of the absorption, distribution, metabolism, and excretion of drugs and other chemical substances that can be used for criminal activities in a legal context. Forensic drug pharmacokinetics face several challenges related to individual variability and the complexities of postmortem drug analysis. Objective: Objective of the current review is to provide a comprehensive overview of all literature related to implications and significance of forensic pharmacokinetics to promote the implication of forensic pharmacokinetics in legal investigation. Methods: Research studies were collected by diversified authentic search engines including: Google Scholar, PubMed, Elsevier, Science Direct, and Springer. The studies that were published during the time span of 2015-2024 were included in the study. Studies were selected, screened and included in the review as per PRISMA. Quality of literature was assessed by Grading of Recommendation Assessment, Development and Evaluation. Results: Findings revealed intoxication accidental or intentional for the cannabiniods, cocaine, benzodiazepines, opioids, methamphetamines, alcohol, ketamine, methadone, anti-depressants and anti-psychotics. Drugs were detected in post-mortem in blood, body fluids, hairs, nails and bones even several months/years’ post death. However, pharmacogenomics, inter-individual differences in drug metabolism, and genetic variability plays a critical role in forensic investigations. Conclusion:Forensic pharmacokinetics plays imperative role in determining intoxication timelines, identifying death causes and linking substance use to criminal behavior. Genetic variability, inter-individual variability, drug interaction, intoxication timelines influence investigations.